Surgical management of cranial fasciitis in infants: on purporse a clinical case - Moreira Holguín, Juan; Oliveros-Rivero, Jorge; Albán-Castro , Sandra; Velez-Ponce, Jazmin; Mejía-Párraga, Yandri (Revista Argentina de Neurocirugía, 2020)
Cranial fasciitis is a benign lesion of smooth muscle tissue, connective tissue and some immune cells, in which can appear as a consequence of a traumatism in the skull. It is very uncommon and its predominance involves one-year-old babies, with a low risk of metastasis. Treatment of choice is complete tumor resection and lowest recurrence rate.A case of a one-year-old girl with cranial fasciitis in frontal region is presented inthis article. Histologically similar to fibrosarcoma, myxoid tumor and fibromatosis, a bibliographic review of the histological characteristics of each pathology to make a good differential diagnosis.
Keywords: Cranial fasciitis, fibrosarcoma, myofibroblastic tumor